DAKWAH ZAKAT: MENYEBARKAN KEWAJIBAN BERZAKAT DI KALANGAN MASYARAKAT PETANI DI KEPULAUAN MERANTI - Imron Rosidi; Maswan Amin (Jurnal Dakwah Risalah, 2019)
Zakat (alms) is an important discourse in a Muslim society so that it is often associated with the economic empowerment of the Ummah (Muslim community at large). This article aims to explain how the efforts made by National Alms Agency of Kepulauan Meranti to use modern instrument and management for disseminating the obligation to pay alms among Muslim people in Kepulauan Meranti. Using observation and interview to get data, BAZNAS has tried intensively to strengthen and improve the society’s consciousness to pay Zakat as piety symbol. This article shows that semi-modern Zakat institution like BAZNAS Kepulauan Meranti conducts complicated negotiation related to religious awareness and problem of modernity. This article also shows how to spread the obligation to pay alms as a never-ending project because the values of religiosity often require elements of modernity. The empty space needed by institutions like BAZNAS is to strengthen the use of modern instruments and modern management implementation in these institutions.